Analysis of Difficulties in 6th-Grade Students of Primary School of Citra Cemara in Listening Comprehension Efforts at YCT Level 3 - Jessy Monica (Fakultas Sastra Universitas Darma Persada, 2023)
Listening comprehension is an essential component of Chinese language education. In addition, Listening comprehension assists students in communicating and comprehending the interlocutor's meaning. This research aimed to determine students' difficulties when answering listening comprehension questions on the YCT test. The research employed qualitative research methods and a descriptive analysis approach. The data and data sources were collected from 38 sixth-grade students using questionnaire and test data collection techniques of Primary School of Citra Cemara academic year 2022/2023. The study's findings indicated that the most common difficulties occurred in parts 3 and 4 of the listening comprehension questions; students frequently selected incorrect answers that did not match the questions. This is predominantly affected by internal factors, such as the student's level of language skills and students dearth of knowledge of social and cultural backgrounds.